A NARRATIVE REVIEW OF THE LATEST DEVELOPMENTS IN ORTHOGNATHIC SURGERY IN INDIA. - Kumar, Vinod (Student’s Journal of Health Research Africa, 2023)
Background Orthognathic surgery has evolved beyond addressing malocclusion and facial aesthetics to include sleep apnea management and aesthetic enhancement. Three-dimensional digital technology integration is now a crucial aspect of orthognathic surgery, improving surgical planning and splint fabrication for enhanced precision. Objective This review aims to elucidate current trends and controversies in orthognathic surgery. It highlights the vital role of plastic surgeons not only in performing surgical procedures but also in establishing surgical occlusion and comprehensive planning. Summary of Narrative Review The integration of advanced digital technology has transformed orthognathic surgery by improving accuracy and precision. This review offers insights into the evolving landscape of orthognathic surgery, addressing emerging trends and ongoing debates. It emphasizes the collaborative role of plastic surgeons and orthodontists in delivering successful outcomes. Implications for Future Research Future research should focus on refining digital technology integration, optimizing surgical planning, and assessing long-term patient outcomes. Exploring innovative techniques and expanding the scope of orthognathic surgery can further enhance patient care. Implications for Clinical Practice and Policy Development Orthognathic surgery’s expanded applications require continuous professional development for plastic surgeons and orthodontists. Healthcare institutions and policymakers should acknowledge the significance of digital technology in surgical practice and provide support and resources for its integration. Additionally, guidelines and standards for orthognathic surgery should evolve to reflect these advancements and ensure patient safety and satisfaction.